Pengelolaan Limbah Padat di Fakultas Kesehatan dan Non Kesehatan Universitas Jember (The Solid Waste Management on Health and Non Health Faculty in University of Jember) - Novita Wahyu Ary Widyaningrum; Rahayu Sri Pujiati; Anita Dewi Moelyaningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Recently, the increase of students in University of Jember also resulting increased of activities.This may cause solid waste also being increase. According to UI’s GreenMetric UniversitySustainability Ranking, University of Jember have tended to decrease in realizing green campuswhich the one of criteria was solid waste management . Based on early study, health and nonhealth faculty was collected in open area in each faculty, being mixed, and burned. This researchaim to describe the solid waste management on health and non health faculty in University ofJember. This research used descriptive observational approach. Unit analysis in this researchwere all health and non health faculty in University of Jember then two health and two non healthfaculty was choosen consist of Public Health Faculty, Faculty of Dentistry, Faculty of Agricultural,and Faculty of Economic. The result of the research showed that Faculty of Economic has thehighest mean weight of solid waste 36,88 kg/day and the mean volume 742,05 liters/day whileFaculty od Dentistry has the lowest mean weight of solid waste 19,38 kg/day and mean volume397,79 liters/day. The conclusion of this research were solid waste management includereduction of solid waste still not comprehensive and handling of solid waste still mixed, heaped inopen place, and burned.Keywords:solid waste, solid waste management, University of Jember.